2021
DOI: 10.11604/pamj.2021.39.139.24667
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with cancellation and deferment of elective surgical cases at a rural private tertiary hospital in Western Uganda: a cross sectional study

Abstract: Introduction the cancellation of elective surgery is still a worldwide challenge and this is associated with emotional and economical trauma for the patients and their families as well as a decrease in the efficiency of the operating theatre. This study aimed at determining the prevalence and factors associated with cancellation and deferment of elective surgery in a rural private tertiary teaching hospital in Western Uganda. Methods a cross-sectional study design was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…In this study out of all departments general surgery had the highest rate of cancellation 19 (50%) and these findings consistent with Asela Teaching Hospital, a rural private tertiary hospital in Western Uganda, Nigeria, Tanzania and Woliata Sodo Hospital, Nort-east India [2,26,30,32,40,41] but in some studies like TikurAnbesa Specialized Hospital, Hawasa Comprehensive Hospital, and Tertiary Hospital in Uganda Orthopedic surgery cancelation has the highest rate of cancelation [15,42,43]. This could be due high burden of patients under general surgery departments which may result in inadequate investigation, lack of ICU beds and operation theatre equipment.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In this study out of all departments general surgery had the highest rate of cancellation 19 (50%) and these findings consistent with Asela Teaching Hospital, a rural private tertiary hospital in Western Uganda, Nigeria, Tanzania and Woliata Sodo Hospital, Nort-east India [2,26,30,32,40,41] but in some studies like TikurAnbesa Specialized Hospital, Hawasa Comprehensive Hospital, and Tertiary Hospital in Uganda Orthopedic surgery cancelation has the highest rate of cancelation [15,42,43]. This could be due high burden of patients under general surgery departments which may result in inadequate investigation, lack of ICU beds and operation theatre equipment.…”
supporting
confidence: 87%
“…This study found that the most common reason for the cancellation was facility/ administrative related which was 40% and it parallel with studies in Tertiary Hospital in Uganda, and Tanzania, Systematic review in Ethiopia, Urban Indian Hospitals [28,42,44,45], but in other studies like the Middle East, rural private tertiary hospitals in Western Uganda, Tikur Anbesa Hospital and Nigeria Teaching Hospital patient-related reasons were the most frequently mentioned reason for cancellation [15,32,33,40]. These causes included lack of theatre space and facilities, unavailability of OT equipment, shortage of logistics Shortage of OR materials, lack of blood prepared and hospital sewerage systems.…”
supporting
confidence: 82%
“…Okeke (2020) found that the 47.5% of the surgery cancellations were attributed to the patient-related factors, including unavailability of the blood products. 13 Kajja (2014) also found that unavailability of the surgical theater was responsible to the surgery cancellation of the surgery in 33.1% of the cases, while the lack of blood products were related to the cancellation of the surgery in 30.1% of the cases. 14 On the other hand, Vahwere (2021) found that only 3.3% of the surgery was cancelled due to the lack of the blood products.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Patients and their families experience inconvenience from a late surgical cancellation, and the financial and logistic impact can be substantial to facilities, which may deal with extended hospital stays and costly repetition of preoperative preparation. [3][4][5] Family members also often do not understand the reasoning behind day-of-surgery case cancellations and require extensive education regarding perioperative risk factors such as potential cardiovascular risk. 6 Analysis of same-day surgical cancellations is important to be conducted by anesthesia, surgical, and administrative personnel, to prevent future costly cancellations.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%